Perceptions of compliance in recreational fisheries: Case study of the Peel-Harvey blue swimmer crab fishery - Lindley, Jade; Quinn, Liam (Frontiers in Conservation Science, 2022)
Effective recreational fisheries management requires a balance between fisher enjoyment and compliance with regulations and fisher perceptions can be useful to understand whether the balance is right. Our study collected fisher insights via an online perceptions survey into compliance within the recreational shore-based Peel-Harvey blue swimmer crab fishery in Western Australia. Overwhelmingly, participants self-reported as complying with regulations; a positive finding for a licence-free fishery. Further, to enable increased quantity and size of available stock and thus overall enjoyment of the fishery, survey participants suggested longer fishery closure periods; harsher noncompliance penalties; more natural and physical surveillance; and greater educational signage in popular fishing areas. These insights challenge existing literature whereby tough regulations are often rejected by fishers and may lead to noncompliance. In a view to achieve a shared goal of a sustainable fishery, we explore survey perceptions against situational crime prevention to optimize compliance, embracing regulator-led ‘cooperative compliance’ outcomes. Our results are useful not only to this fishery but apply more broadly to other fisheries within and beyond Western Australia.